Exploration Of Digital-Based Consumptive Behavior E-Lifestyle In Generation–Z - Ratnaningsih Sri Yustini; Dyah Rini Prihastuty (Jurnal Ekonomi, 2024)
Exploring consumer behavior based on digital e- lifestyle in generation Z is an increasingly relevant topic in the context of the current digital era. Generation Z, who grew up amidst advances in digital technology, has experienced significant changes in their consumer behavior patterns. This research aims to investigate the factors that influence generation Z's consumer behavior in the context of their digital e-lifestyle . This research uses primary data collected using survey methods. The sampling technique used in this research is purposive sampling, where respondents are required to meet the criteria set by the researcher. The research results show that generation Z buyer behavior is strongly influenced by social media, where they are exposed to trends, brands and lifestyles promoted by digital influencers. Additionally, the convenience and flexibility of online shopping also plays an important role in their consumption decisions. Another significant factor is the FOMO ( Fear of Missing Out ) phenomenon, where generation Z feels the need to engage in activities and own items that match their friends in order to maintain social relevance. Additionally, digital identity and self-expression are also important factors in their consumption decisions, where they use goods and services to strengthen their self-image in the online world. However, the importance of sustainability is also emerging as an increasingly important consideration for generation Z, who tend to choose brands that are highly socially and environmentally responsible. By understanding these factors, companies and organizations can develop more effective strategies in targeting generation Z as their consumers, while also paying attention to the social, environmental and psychological impacts of this digital e- lifestyle based consumer behavior. Further research is needed to gain a deeper understanding of changes in generation Z's consumer behavior along with the development of digital technology and changing social dynamics.